PERSPECTIVE OF COGNITIVE THINKING AND REFLECTIVE TEACHING PRACTICE - Jelena Maksimović; Jelena Osmanović (International Journal of Cognitive Research in Science, Engineering and Education, 2019)
The factor analysis was used to ascertain the factors reflecting the most important attitudes of the respondents concerning reflective thinking in the classroom: self-evaluation, feedback and recording, improvement and analysis of teaching materials, assessment, concepts and misconceptions, construction of knowledge, metacognition and permanent improvement. The results of this research showed statistically significant differences among the aforementioned factors concerning the cycle of education (elementary school teachers and middle school teachers) and work experience (0-5, 6-10; 11-20; over 20 years of experience). The differences were obtained by parametric statistics, calculated using the t test and ANOVA test, p<0.05.